Clockwise hairpin‐type metamorphic pressure–temperature (P–T) path recorded in the Shangla blueschist along the Indus Suture Zone, Pakistan Himalaya. Issue 11 (10th June 2020) - Iqbal, Muhammad Zahoor; Li, Weimin; Ali, Asghar; Liu, Yongjiang; Zhang, Duo
Abstract : The Shangla blueschist, exposed along the Indus Suture Zone, Pakistan Himalaya, have been petrologically investigated in order to elucidate their tectono‐metamorphic evolution, and to better understand the geodynamic scenario of intra‐oceanic subduction between the Indian Plate and Kohistan‐Ladakh Arc. Representative mineral assemblages identified from the Shangla blueschist, contain amphiboles (glaucophane, magnesioriebeckite, winchite, actinolite, edenite, and magnesiohornblende), epidote, phengite, albite, chlorite, titanite, rutile, quartz, and haematite. Three distinct metamorphic stages are recognized for the Shangla blueschist. An early prograde (pre‐peak) metamorphic stage (M1) is characterized by the presence of winchite as the core part of zoned amphiboles, together with inclusions of epidote, albite, chlorite, quartz, titanite, and haematite in epidote porphyroblasts. This stage roughly reveals a temperature range of 300–450°C and pressures of 0.4–0.7 GPa. The equilibrium minerals of peak (M2) metamorphic stage consist of matrix, schistosity‐forming minerals including amphiboles (glaucophane, magnesioriebeckite), epidote and phengite, with fine‐grained rutile, titanite, and haematite in albite porphyroblasts, suggesting P – T condition of 350–520°C and 0.9–1.2 GPa. The retrograde (M3) metamorphic stage involved overgrowth of winchite and actinolite along glaucophane rims, and chlorite replacement of amphibole as well as growth of albite porphyroblasts, representing the greenschist‐facies metamorphism. Our obtained peak P–T metamorphic condition (epidote‐blueschist facies) is significantly higher than previously estimated P–T ranges of 400°C/0.7 GPa. Moreover, the retrograde approximately reversed prograde trajectory defines a hairpin‐type P–T path for the Shangla blueschist, similar to the Franciscan ‐ type metamorphism that is characterized by relatively slow exhumation after peak stage with the decompression accompanied by cooling process. Taking the published geochronological data into account, these new results provide insights into the metamorphic evolution of the Shangla blueschist during ca. 80 Ma (Late Cretaceous) from burial by cold subduction of the Neo‐Tethys to subsequent post‐peak exhumation. Furthermore, the exhumation mechanism of the Shangla blueschist is most likely driven by a combined effect of both underplating and later thrust faulting, probably during the collision of the Indian Plate and Kohistan‐Ladakh Arc.